THE ARAB REPRESENTATION OF EUROPEAN DEMOCRATIC VALUES AND ITS INFLUENCE ON EURO-ARAB RELATIONS - NOHRA, Fouad (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2018)
The drive for a research on the Euro-Arab cultural interaction and on the influence of European patterns of democracy is motivated by a serious concern about the superficial statements which is often displayed by the past studies on public opinion, some of them assuming that the European political model of democracy is ab initio rejected by the Arab societies.